2021
DOI: 10.1098/rspa.2020.0701
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-enabled road condition monitoring: from accelerations to road roughness and excess energy dissipation

Abstract: We develop a framework to address the shortcomings of current smartphone-based approaches for road roughness sensing and monitoring through combining vehicle dynamics, random vibration theory and a two-layer inverse analysis. The proposed approach uses in-cabin recordings of the vehicle’s vertical acceleration measured by a smartphone positioned inside the car for the estimation of road roughness. The mechanistic road roughness–vehicle interaction model at the core of the proposed framework links the frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…However, Hanson et al [94] reported a limited impact of speed change from 50 to 80 km/h in their study. Additionally, Botshekan et al [97] reported a lower impact of speed variation for larger-scale surveys.…”
Section: Acceleration-based Response-type Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, Hanson et al [94] reported a limited impact of speed change from 50 to 80 km/h in their study. Additionally, Botshekan et al [97] reported a lower impact of speed variation for larger-scale surveys.…”
Section: Acceleration-based Response-type Approachesmentioning
confidence: 99%
“…For example, Hanson et al [94] reported that the difference between the measured IRI and the reference value varied from 5.4% to −11.9% when measured using a compact car (2001 Pontiac Sunfire) and a sport utility vehicle (2011 Nissan Rogue), respectively. However, Botshekan et al [97] indicated that well-trained machine learning models could be used for different types of vehicles. Additionally, Jeong et al [102] suggested that the use of gyration (i.e., angular velocity) can minimize the effect of vehicle model variation.…”
Section: Acceleration-based Response-type Approachesmentioning
confidence: 99%
See 3 more Smart Citations